Analysis of construction markets in Ukraine: current state, trends and directions of activation - Kutsenko , A. (Ways to Improve Construction Efficiency, 2025)
The article is devoted to a comprehensive analysis of the construction markets of Ukraine in the conditions of war and post-war transformations, covering a period of sharp changes in the economic, social and institutional prerequisites for the functioning of the industry. The work substantiates that the construction sector occupies a key place in the processes of restoring the national economy, as it ensures the modernization of damaged infrastructure, the formation of new spatial development structures and support for related industries. The study shows that, despite high risks, a shortage of labor resources, logistical constraints and a general decrease in investment activity in certain regions, the construction market demonstrates adaptability and gradual stabilization.The article identifies and analyzes key trends that determine the current dynamics of the market: a shift in priorities from new construction to reconstruction and reconstruction works; increasing regional asymmetry between safer regions and frontline areas; structural shifts in market competition due to a decrease in the number of active contractors and an increase in the role of large integrated companies. Considerable attention is paid to digital transformations, in particular, the implementation of the Unified State Electronic Procurement System and digital public procurement tools, which create new opportunities for increasing transparency and reducing corruption risks. The authors identify strategic directions for activating the construction market, among which the development of innovative construction technologies, increasing human resource capacity, improving the regulatory and institutional environment, stimulating investments, and forming flexible approaches to managing the competitiveness of enterprises are of practical value for state authorities, development institutions, development companies, and contracting organizations, as they contribute to the formation of an effective reconstruction policy and a long-term strategy for the sustainable development of the construction industry of Ukraine.